Impacts of land developments and land use changes on urban stormwater management - Basnayaka, Amila Prasad (Curtin University, 2012)
With the rapid urbanization happening around the world, the nature of the natural hydrological cycle has been changed and it causes many adverse effects like urban flooding, erosion and degradation of water quality in urban areas. Due to the increasing population, urbanization will continue rapidly and this increases impervious lands which generate more runoff. Anthropogenic climate change has influenced the strength of storm events and reduced the recurrent intervals. Current urban stormwater management systems are becoming increasingly lacking with rapidly increasing demands and climatic effects. Groundwater has been found as a key factor in creating inadequacy in urban drainage to carry stormwater runoff in catchments having a shallow groundwater table. Water sensitive urban design (WSUD) and modifications to urban stormwater management systems (USWMSs) according to the best management practices (BMP) should be implemented after systematic analysis to overcome the situation.This study has focused on assessing urban land development activities and changing patterns of land use in urban areas as the main anthropogenic stress on urban hydrology. In addition, the adaptation to natural phenomenon such as climate change has been studied. A numerical hydrological model was used to analyse the behaviour of catchments and their characteristics. Urban flood identification and prevention was one of the major concerns of this study. Several urban stormwater drainage systems have been assessed under three case studies.The stormwater drainage system of Canning Vale Central catchment, which is one of the urban catchments in Western Australia, has been assessed by using numerical modelling in case study number one. The model was developed by using existing mapped data and data collected from an ongoing telemetric observation system and several field visits. Surface runoff has been routed by using different modelling techniques such as hydrological surface runoff and two-dimensional (2D) surface runoff modelling. Groundwater has been treated as a critical issue during the modelling. The effects of land use changes and their sensitivity to the USWMS have been assessed. Necessary recommendations to improve the USWMS and mitigate localised flood issues have been given. Flood vulnerability maps have been developed to identify the critical areas where there is the potential to be flooded under different Average Recurrent Interval (ARI) events. These flood vulnerability maps will be used by the local authorities to develop recommendations and guidelines for future developments of infrastructure during land development and subdivision works.The urban ungauged catchment of Victoria Park in Western Australia has been assessed by using a 2D surface runoff routing model. The catchment has built flood storage areas (stormwater basins) and the inadequacy of them in protecting against recent storm events has caused local concern. The area has been developed rapidly in recent decades and land use has been changed to more impervious surfaces than was expected at the time the basins were designed. These changes to the land use—together with anthropogenic climate change—has caused runoff from rapid storms to exceed the basin top water level. The catchment‘s existing stormwater basins‘ capacities were assessed against different ARI events during case study number two. Flood vulnerability maps and water level contours have been developed to identify the possible inundations and flood depths of basins and surrounding areas.The overall study is based on hydrological modelling of different USWMSs and urban hydrology. Land use change was considered as the main anthropogenic stress upon urban hydrological catchments. Factors such as encountering groundwater in stormwater drainage have been analysed to support the study. Recommendations based on WSUD and BMPs have been given to mitigate the adverse effects of urban land use changes to urban stormwater management.